Cardiology - Gray, Huon H.; Dawkins, Keith D.; Morgan, John M.; Simpson, Iain A. (The lecture notes series, 2008)
Lecture Notes: Cardiology is a comprehensive introduction to one of the most rapidly changing specialities in clinical medicine. This informative and highly accessible book presents clinical cardiology in a way that relates disease to underlying pathophysiological mechanisms, and links this directly to the patient, their disease and its management. This fifth edition has been thoroughly revised and updated and remains a firm favourite with students for its: Strong focus on the clinical approach, Full-colour illustrations throughout including Doppler images, clinical photographs, ECG traces and flow charts More comprehensive coverage of congenital heart disease, Thorough coverage of the cardiology curricula.